2007
DOI: 10.1159/000107956
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Primary Renal Carcinoma Cultures

Abstract: Purpose: For a better understanding of the factors contributing to tumor progression in metastatic renal cell carcinoma and to identify possible targets for immunotherapeutic approaches, we characterized several primary cultures from renal cell carcinoma. Materials and Methods: Cell cultures were tested for activity of telomerase, secretion of immunosuppressive cytokines and others. The induction of cytotoxic activity against the autologous tumor was tested in a cytotoxicity assay after coculture of immunologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 48 publications
0
7
0
Order By: Relevance
“…Interestingly, elevated levels of TGF-β1 in serum from CCRCC patients are correlated with unfavorable outcome of the disease [26], [28], [29]. Hence, the tumor microenvironment in CCRCC is rich in TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, elevated levels of TGF-β1 in serum from CCRCC patients are correlated with unfavorable outcome of the disease [26], [28], [29]. Hence, the tumor microenvironment in CCRCC is rich in TGF-β1.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, gene expression studies in large cohorts of RCC-bearing patients have suggested that some molecules such as IL-1, IL-6, TNF-α, C1q, and C1r could be implicated in the initiation and promotion of an intratumor inflammatory cascade (Peri, Devarajan, Yang, Knudson, & Balachandran, 2013;Romero et al, 2006;Tan et al, 2011). The RCC tumor cells probably orchestrate this inflammatory environment as suggested by the presence of several cytokines in the supernatant of RCC primary cultures, including IL-8, IL-10, TGF-β, GM-CSF, TNF-α, and VEGF (Gogusev, Augusti, Chrétien, & Droz, 1993;Knoefel et al, 1997;Lahn et al, 1999;Lee, Chun, Nadiminty, Lou, & Gao, 2007;Sievers et al, 2007). Interestingly, some of them can be found in the serum of RCC-bearing patients Wald et al, 2014), supporting their active production throughout RCC development.…”
Section: The Ccrcc Tumor Microenvironmentmentioning
confidence: 99%
“…IL-6 is secreted by many renal cancer cell lines and is abundant in the serum of 50% of the patients with metastatic [39,40] renal cell cancer [39][40][41][42]. Moreover, it has been demonstrated that primary RCC cultures secrete elevated levels of IL-6 [43]. Investigated RCC cell lines expressed IL-6 mRNA, produced IL-6, and expressed the soluble and membrane-bound gp130 chain of the IL-6 receptor.…”
Section: Il-6 and Rccmentioning
confidence: 99%